Exploring the Therapeutic Potential of Urtica Urens in Homoeopathic Practice: Novel Approach to Urticaria Management – A Case Report (Homoeopathy for All, 2024)
Urticaria is an itchy rash associated  with localized swelling (angioedema)  on the skin that usually lasts for few  hours to days before fading away. It  is also known as hives.  =Urticaria also called nettle-rash  or hives or wheals in a common  language, simply means itching  with rash. Medically, urticaria  may be defined as skin eruption,  which is allergic in origin and is  characterized by profound itching,  red, circular or irregularly shaped  eruptions on any part of the body.  Urticaria is an allergic skin disorder.  Characteristically the skin eruptions  are erythematous, raised above the  skin level, with intense itching and  usually worsened by itching and  with slight local warmth.
Keywords: Angioedema; Erythema; Nettle-rash; Hives; Mastocytosis; Histamine; IgE